2020
DOI: 10.1136/bmjsrh-2020-200741
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum long-acting contraception uptake and service delivery outcomes after a multilevel intervention in Kigali, Rwanda

Abstract: IntroductionPostpartum family planning (PPFP) is critical to reduce maternal–child mortality, abortion and unintended pregnancy. As in most countries, the majority of PP women in Rwanda have an unmet need for PPFP. In particular, increasing use of the highly effective PP long-acting reversible contraceptive (LARC) methods (the intrauterine device (IUD) and implant) is a national priority. We developed a multilevel intervention to increase supply and demand for PPFP services in Kigali, Rwanda.MethodsWe implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…which was provided to 12,068 pregnant and postpartum women/couples in health facilities and the surrounding community. During our pilot, LARC uptake up to 6 weeks after delivery increased significantly (with 3372 PPIUD inserted representing a 2710% increase compared to the 6 months prior to our pilot, and 1252 implants inserted representing a 178% increase compared to the 6 months prior to our pilot), PPFP feasibility and acceptability were high among providers and clients, and side-effects were rare [5,6].…”
Section: Background and Rationale {6a}mentioning
confidence: 82%
See 1 more Smart Citation
“…which was provided to 12,068 pregnant and postpartum women/couples in health facilities and the surrounding community. During our pilot, LARC uptake up to 6 weeks after delivery increased significantly (with 3372 PPIUD inserted representing a 2710% increase compared to the 6 months prior to our pilot, and 1252 implants inserted representing a 178% increase compared to the 6 months prior to our pilot), PPFP feasibility and acceptability were high among providers and clients, and side-effects were rare [5,6].…”
Section: Background and Rationale {6a}mentioning
confidence: 82%
“…All facilities have the infrastructure for PPFP provision and procurement; though no formal PPFP initiatives are currently taking place, PP implant insertions are infrequent, and no providers are trained to insert PPIUDs. Our team has worked in these clinics (conducting clinic logbook data abstraction, implementing couples' HIV counseling and testing, implementing interval LARC services, and surveying providers and patients) for over 10 years [6,[14][15][16][17][18][19][20][21].…”
Section: Study Setting {9}mentioning
confidence: 99%
“…The studies werereported from 37 countries, from all regions, and from LMIC and High-income countries. Eight studies were reported from the USA [ 27 34 ]; four from Tanzania [ 35 – 38 ], two from Sri Lanka [ 39 , 40 ], Nigeria [ 41 , 42 ], Nepal [ 43 , 44 ], Rwanda [ 45 , 46 ], Bangladesh [ 38 , 47 ], and one study from Benin [ 48 ], Bolivia [ 49 ], Burkina Faso [ 50 ], Chad [ 48 ], Côte d’Ivoire [ 48 ], Democratic Republic of Congo [ 50 ], Guatemala [ 51 ], India [ 52 ], Liberia [ 53 ], Mexico [ 49 ], Niger [ 48 ], Pakistan [ 54 ], Senegal [ 48 ], Togo [ 48 ], and Turkey [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…A pre-intervention insertion rate of 7.7 PPIUDs/ month, increased to 214.6 insertions/month. [7] This study is an example of addressing contraceptive insufficiencies by targeting multiple levels of care and counselling patients at multiple visits and having the capacity to provide chosen contraception as desired. An intervention of this scale within our communities may influence any stigma associated with LARCs and help to increase LARC uptake Many HIV-positive patients in the intervention group of this study showed interest in the use of an implant, but because of the current national policy of not providing implants to HIV-positive women using enzyme-inducing treatment, were counselled against this choice.…”
Section: Discussionmentioning
confidence: 99%